Induced Pluripotent Stem Cell for the Study and Treatment of Sickle Cell Anemia - Luiza Cunha Junqueira Reis; Virgínia Picanço-Castro; Bárbara Cristina Martins Fernandes Paes; Olívia Ambrozini Pereira; Isabela Gerdes Gyuricza; Fabiano Tófoli de Araújo; Mariana Morato-Marques; Lílian Figueiredo Moreira; Everton de Brito Oliveira Costa; Tálita Pollyanna Moreira dos Santos; Dimas Tadeu Covas; Lygia da Veiga Pereira Carramaschi; et al. (Hindawi Limited, 2017)
Sickle cell anemia (SCA) is a monogenic disease of high mortality, affecting millions of people worldwide. There is no broad, effective, and safe definitive treatment for SCA, so the palliative treatments are the most used. The establishment of an in vitro model allows better understanding of how the disease occurs, besides allowing the development of more effective tests and treatments. In this context, iPSC technology is a powerful tool for basic research and disease modeling, and a promise for finding and screening more effective and safe drugs, besides the possibility of use in regenerative medicine. This work obtained a model for study and treatment of SCA using iPSC. Then, episomal vectors were used for reprogramming peripheral blood mononuclear cells to obtain integration-free iPSC. Cells were collected from patients treated with hydroxyurea and without treatment. The iPSCP Bscd lines were characterized for pluripotent and differentiation potential. The iPSC lines were differentiated into HSC, so that we obtained a dynamic and efficient protocol of CD34+CD45+ cells production. We offer a valuable tool for a better understanding of how SCA occurs, in addition to making possible the development of more effective drugs and treatments and providing better understanding of widely used treatments, such as hydroxyurea.